Subthalamic deep brain stimulation for primary dystonia: defining an optimal location using the medial subthalamic nucleus border as anatomical reference - Zhao, Mingming; Chen, Hui; Yan, Xin; Li, Jianguang; Lu, Chao; Cui, Bin; Huo, Wenjun; Cao, Shouming; Guo, Hui; Liu, Shuang; Yang, Chunjuan; Liu, Ying; et al. (Frontiers in Aging Neuroscience, 2023)
Introduction Although the subthalamic nucleus (STN) has proven to be a safe and effective target for deep brain stimulation (DBS) in the treatment of primary dystonia, the rates of individual improvement vary considerably. On the premise of selecting appropriate patients, the location of the stimulation contacts in the dorsolateral sensorimotor area of the STN may be an important factor affecting therapeutic effects, but the optimal location remains unclear. This study aimed to define an optimal location using the medial subthalamic nucleus border as an anatomical reference and to explore the influence of the location of active contacts on outcomes and programming strategies in a series of patients with primary dystonia. Methods Data from 18 patients who underwent bilateral STN-DBS were retrospectively acquired and analyzed. Patients were assessed preoperatively and postoperatively (1 month, 3 months, 6 months, 1 year, 2 years, and last follow-up after neurostimulator initiation) using the Toronto Western Spasmodic Torticollis Rating Scale (for cervical dystonia) and the Burke–Fahn–Marsden Dystonia Rating Scale (for other types). Optimal parameters and active contact locations were determined during clinical follow-up. The position of the active contacts relative to the medial STN border was determined using postoperative stereotactic MRI. Results The clinical improvement showed a significant negative correlation with the y-axis position (anterior–posterior; A+, P−). The more posterior the electrode contacts were positioned in the dorsolateral sensorimotor area of the STN, the better the therapeutic effects. Cluster analysis of the improvement rates delineated optimal and sub-optimal groups. The optimal contact coordinates from the optimal group were 2.56 mm lateral, 0.15 mm anterior, and 1.34 mm superior relative to the medial STN border. Conclusion STN-DBS was effective for primary dystonia, but outcomes were dependent on the active contact location. Bilateral stimulation contacts located behind or adjacent to Bejjani’s line were most likely to produce ideal therapeutic effects. These findings may help guide STN-DBS preoperative planning, stimulation programming, and prognosis for optimal therapeutic efficacy in primary dystonia.